Measurement of Uranium Concentrations in Human Blood in Some the Regions of Baghdad Governorate - Karim, M. S.; Mohammed, A.H.; Abbas, A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this research is to determine the concentrations of uranium in human blood in some regions of Baghdad governorate and to determine the level of contamination with uranium for these regions during the (2003) war. The results obtained have shown that the maximum uranium concentration in blood samples was found (0.256 ppm) in AL-Zaifranea region and AL-Sader city,while the minimum in AL-Shab region (0.052 ppm) ,the minimum of uranium concentration in the blood samples was found to be (0.008 ppm) (male,39 years old) lived in AL-Shab region, while the maximum of uranium concentration in the blood samples was found to be (0.44 ppm) (female, 55 years old ) lived in  AL-Sader city.